Hopping transport in nanogranular composite films of FeCoZr alloy nanoparticles deposited into Al2O3 and PZT dielectric matrices - Larkin, Andrei V.; Fedotov, Alexander K. (Journal of the Belarusian State University. Physics, 2023)
The paper presents the study of hopping carrier transport parameters (characteristic times and energies) in nanogranular composite films (Fe0,45Cо0,45 Zr0,10 )x(Al2O3)1 – x and (Fe0,45Cо0,45Zr0,10)x(PZT)1 – x with a concentration of metalcontaining nanoparticles inside of insulator matrix in the range 0.3 < х < 0.8. Films of 2–7 µm thick were obtained by ion-beam sputtering of composite targets in pure argon gas or in Ar – O2 mixture, after which they were subjected to stepwise post-annealing in air in the temperature range of 398-873 K with the 25 K steps for 15 min. Deposition of the films in the argon – oxygen gas mixture or their post annealing led to the formation of metal-containing nanoparticles with core – shell structure, where the covering shell contained own iron and cobalt oxides (FeO, Fe3O4, Fe2O3, CoO). It was shown that the behaviour of concentration, frequency and temperature dependences of specific admittance σ (x, ω, T) is controlled by two critical values of nanoparticles’ concentrations – touching threshold (хс1) and conducting cluster formation threshold (хс2 ) (in contrast to a single percolation threshold (хс ) in the theory for binary metal-dielectric composites). The хс1 is the concentration when some of nanoparticles inside the dielectric matrix begin to touch each other by shells to form continuous core – shell cluster with high current conductivity between electrodes in the composite sample. Since the conductivity of such a core-shell cluster is always less than the conductivity of only metallic nanoparticles, as in binary composites, we introduce another threshold concentration хс2 when the metallic cores of nanoparticles begin to touch each other. We observed that, when composite film approaches the хс1 threshold, the characteristic lifetime τ of electrons, extracted from σ (x, ω, T) dependences, on nanoparticles covered with the semiconducting-like shells of native oxides (FeO or Fe3O4 ) increases from 0.1 to 400.0 µs. For this case, we observed a positive phase shift θ between the applied voltage and current in the films, called the negative capacitance effect. At the same time, energy characteristics ∆E1 and ∆E2 extracting from σ(T) dependences were decreased down to values less than phonon energy kT – from 300 to 1 meV. In the case of the predominance of native oxide of iron with insulating properties (Fe2O3) around the nanoparticles, there is no increase in τ and a decrease in ∆Ei. In this case the usual capacitive-like behaviour of nanocomposites with a negative phase shift θ between current and voltage is observed.
Keywords: nanogranular composites; core – shell nanoparticles; hopping transport; negative capacitance effect